Fenaminosulf Promotes Growth and Gall Formation in Zizania latifolia Through Modulation of Physiological and Molecular Pathways - Chaohong Ding; Ruifang Ma; Liqiu Wang; Xinyan Lan; Limin Chen; Jinxing Zhu; Lailiang Wang (Plants)
Zizania latifolia (Jiaobai) is an economically important aquatic crop characterized by unique gall formation through interaction with the smut fungus Ustilago esculenta. Understanding factors influencing this interaction is crucial for cultivation. This study investigates the non-target effects of the fungicide Fenaminosulf (FM) on Z. latifolia’s growth, physiology, and underlying molecular pathways. We demonstrate that FM exerts striking concentration-dependent effects, revealing its potential as a modulator of plant development and symbiosis. Physiological measurements showed that a moderate FM concentration (1.25 g/L) promoted key vegetative growth parameters, including plant height and leaf length, while maintaining chlorophyll content, suggesting a potential bio-stimulant effect. In contrast, higher FM concentrations (2.5 g/L and 5 g/L) inhibited vegetative growth but significantly enhanced gall formation, particularly at 2.5 g/L, indicating that FM can redirect plant resources or alter susceptibility to favor the fungal interaction under specific conditions. Transcriptomic analysis provided mechanistic insights, revealing extensive gene expression reprogramming, especially under high FM treatment (5 g/L). Key pathways related to plant-pathogen interaction, phenylpropanoid biosynthesis, and hormone signal transduction were significantly modulated. Notably, FM treatment suppressed key immune-related genes, including Xa21 and PBL19, potentially reducing plant resistance and facilitating gall formation. Hormone signaling analysis revealed inhibition of auxin, cytokinin, brassinosteroid, and jasmonic acid metabolism, indicating a comprehensive molecular recalibration of plant developmental processes. The study provides novel insights into the molecular mechanisms by which FM influences Z. latifolia growth and gall formation. The concentration-dependent effects of FM suggest its potential as a strategic tool for agricultural management, offering a nuanced approach to crop development. These findings contribute to understanding plant-chemical interactions and provide valuable directions for optimizing Z. latifolia cultivation strategies.